The effect of COVID-19 pandemic on the mental health of Canadian critical care nurses providing patient care during the early phase pandemic: A mixed method study. (April 2021) - Crowe, Sarah; Howard, A. Fuchsia; Vanderspank-Wright, Brandi; Gillis, Paula; McLeod, Fiona; Penner, Caroline; Haljan, Gregory
Abstract: Background: Healthcare workers have historically experienced symptoms of post-traumatic stress disorder, depression and anxiety with previous infectious outbreaks. It is unknown if critical care nurses have similar experiences. Objectives: The study aimed to examine the mental health of Critical Care Registered Nurses providing direct patient care during the initial phase of the COVID-19 pandemic in Canada. Design: This was a convergent parallel mixed method study utilizing validated questionnaires and semi-structured qualitative interviews. Setting: Critical care units in a single large 650 bed academic teaching hospital in western Canada. The critical care units serve a general mixed medical – surgical adult patient population. Participants: Critical Care Registered Nurses providing direct patient care in the intensive care and high acuity units at the designated site. Methods: 109 participants completed two self-reported validated surveys, the Impact of Events Scale – Revised and the Depression, Anxiety and Stress Scale. 15 participants completed one-on-one semi-structured interviews that were analyzed using inductive thematic analysis. Results: In the surveys, the participants reported clinical concern for (23%), probable (13%) and significant (38%) symptoms of post-traumatic stress disorder, as well as mild to severe depression (57%), anxiety (67%) and stress (54%). In the interviews, psychological distress was described as anxiety, worry, distress and fear related to: 1) rapidly changing policy and information, 2) overwhelming and unclear communication, 3) meeting patient care needs in new ways while staying safe, and 4) managing home and personal commitments to self and family. Conclusions: Critical care nurses experienced psychological distress associated with providing care to COVID-19 patients during the early phases of the pandemic.